2018
DOI: 10.1002/elan.201800071
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Pathways and Identification of the Electrochemically Generated Oxidation Products of Flavonoid Eriodictyol in the Presence of Glutathione

Abstract: The metabolic oxidation pathways of dietary flavonoid eriodictyol (Er) are not very well‐probed. In the present work, the electrochemical oxidation behavior of Er was studied in aqueous Britton‐Robinson (B‐R) buffer solution using cyclic voltammetry (CV), chronoamperometry (CA), and bulk‐electrolysis (BE). The oxidation products and reaction pathways of Er in the absence and the presence of glutathione (GSH) were proposed and identified in view of the results obtained by ultra‐high‐performance liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The behavior of KC in the oxidation process was similar to what was observed previously in procyanidin B2 [27]. A previous study reported that the hydroxyl groups of the catechol B ring are more easily oxidized than those of the resorcinol A ring [29,30]. When the potential scan is switched at +0.9 V, the anodic peak at +0.59 V indicates a reversible reaction (inset in Figure 2, blue voltammogram).…”
Section: Voltammetric Behavior Of Kc On Gcesupporting
confidence: 83%
“…The behavior of KC in the oxidation process was similar to what was observed previously in procyanidin B2 [27]. A previous study reported that the hydroxyl groups of the catechol B ring are more easily oxidized than those of the resorcinol A ring [29,30]. When the potential scan is switched at +0.9 V, the anodic peak at +0.59 V indicates a reversible reaction (inset in Figure 2, blue voltammogram).…”
Section: Voltammetric Behavior Of Kc On Gcesupporting
confidence: 83%
“…Secondly, the objective was to use the polyphenol solution when GSH is present in excess (1.0 mM) and then flow it through the cell of electrolysis (method 2). This approach ensured that there was an ample amount of GSH available to react with the polyphenols, facilitating the desired reactions within the electrolysis cell [51]. By employing these two distinct methods, it aimed to explore different approaches for handling oxidized polyphenols and GSH in the electrochemical cell.…”
Section: Bulk-electrolysis Flow-cell System For the Oxidation Of Poly...mentioning
confidence: 99%
“…PAs become more hydrophobic in an acidic medium due to their nonionizing OH groups, which migrate on the hydrophobic surface of a GCE and adsorb there. By becoming more ionizable in the basic medium, the OH groups make the PAs molecule more hydrophilic and migrate away from the surface of the GCE to the bulk solution [57]. As a result, the electroactive species of PAs (i.e., nonionizable forms) are more concentrated at acidic pH levels than at basic pH levels.…”
Section: Effect Of Ph On the Cyclic Voltammetric Behavior Of Proantho...mentioning
confidence: 99%